البنية التّركيبيّة في قصيدة أبناء الوطن للشّاعر معروف الرّصافي - قرنيط, بوقرحة, عبد العالي الياس (Univesity of El-Oued, 2022)
الحمد لله الذي وفقنا لإتمام هذا البحث المتواضع , و الصلاة و السلام علي رسول الله صلى الله عليه و سلم و بعد : يتلخص هذا البحث في ذكر آليات تحليل البنية التّركيبيّة في قصيدة " إلى أبناء الوطن " للشاعر معروف الرصافي في أن : آليات البنية التّركيبيّة كثيرة و متعدّدة أهمها : أنماط التّركيب , الرّبط ,الارتباط , الانزياح, الأساليب , كما أن أنماط التّركيب تختلف باختلاف نوع الجملة , فالجملة الفعلية مدلولها الحركية و الاسمرار و الجملة الاسميّة مدلولها الثبات و الاستقرار , و نجد أيضا أن أدوات الرّبط عند العرب و الغربيين كما يلي: عند العرب : الربط عن طريق: العطف و الجر وأدوات نصب الفعل المضارع و أدوات الشرط .. , أما عند الغربيين : الربط بالأداة الوظيفيّة و هو ما عبر عنه النحويون بالربط بالأداة مثل الحروف و غيرها و الربط عن طريق الإلحاق بالعطف و هو ما عبر عنه بالربط بالحرف " الواو" بصفة خاصة , و الربط بالمفردات الفارغة و هو ما عبر عنه النحويون الربط بالأدوات أيضا , و اختلفت أدوات الارتباط بين العرب و الغربيين , فوجدنا : عند العرب : علاقة الإسناد , علاقة التّعدية , علاقة الإضافة , علاقة الوصفية ... و غيرها , أما عند الغربيين فتجلت في الارتباط الإسنادي و هو نفسه ما ذكره النحويون بعلاقة الإسناد , الارتباط عن طريق الإلحاق بالتبعية و هو ما عبر عنه النحويون بعلاقة الارتباط عن طريق الوصف . كما أن الانزياح ظهر جليا في القصيدة عن طريق : التّقديم و التأخير , و الحذف . وقد شملت القصيدة مجموعة من الأساليب الإنشائيّة منها : الأمر , النّداء , الاستفهام , التّعجب ... و هي بدورها تنقسم إلى إنشاء طلبي و غير طلبي , و أيضا شملت القصيدة مجموعة من الأساليب الخبرية منها : النّفي , المدح و الذم و التّحسر ... و هذا أهم ما تمكنا من التوصل إليه من آليّات تحليل البنية التّركيبيّة في القصيدة . Praise be to God, who enabled us to complete this humble research, and may blessings and peace be upon the Messenger of God, may God’s prayers and peace be upon him, and after: The mechanisms of structural structure are many and varied, the most important of which are: patterns of structure, linkage, association, displacement, methods, and patterns of structure differ according to the type of sentence. And the Westerners are as follows: For Arabs: linking through: conjunction, ablative, present tense accusative tools, and conditional tools.. As for Westerners: linking with the functional tool, which is what the grammarians expressed by linking to the tool such as letters and others, and linking by appending kindness Which is expressed by linking with the letter “waw” in particular, and linking with empty vocabulary, which is what grammarians expressed as linking with tools, and the linking tools differed between Arabs and Westerners, and we found: among Arabs: attribution relationship, transitive relationship, addition relationship, The descriptive relationship ... and others, but for Westerners it manifested itself in the attribution relationship, which is the same as what the grammarians mentioned about the attribution relationship, the link by appending to dependence, which is what the grammarians expressed about the link relationship through description. The displacement is also evident in the poem through: introduction, delay, and omission. The poem included a set of construction methods, including: the command, the appeal, the question, the exclamation ... which in turn is divided into creating my request and non-request, and also the poem included a group of declarative methods, including: denial, praise, slander and bemoan... And this is the most important thing that we have been able to reach from the mechanisms of analyzing the structural structure in the poem
Keywords: البنية، التركيب، مستويات اللغة، الانزياح، الربط، الارتباط، الأسلوب، الجملة.; Structure، Composition، language levels، displacement، Connectivity، link،